Promising Antineoplastic Actions of Melatonin - Favero, Gaia; Moretti, Enrico; Bonomini, Francesca; Reiter, Russel J.; Rodella, Luigi Fabrizio; Rezzani, Rita (Frontiers in Pharmacology, 2018)
Melatonin is an endogenous indoleamine with an incredible variety of properties and activities. In recent years, an increasing number of studies have investigated this indoleamine’s interaction with cancerous cells. In particular, it seems that melatonin not only has the ability to improve the efficacy of many drugs used in chemotherapy, but it also has a direct inhibitory action on neoplastic cells. Many publications underlined the ability of melatonin to suppress proliferation of various cancer cells or to modulate the expression of membrane receptors on these cells, thereby, reducing tumor aggressiveness to metastasize. Also, while melatonin has anti-apoptotic actions in normal cells, in many cancer cells it has pro-apoptotic effects and these dichotomous actions have emerging and growing interest. The increasing concern on melatonin in the oncologic field and the mounting number of studies on this topic require a deep understanding of what we already know about anti-neoplastic actions of melatonin. This information would be of value for a potential use of melatonin against neoplastic diseases.